In Silico Evidence That Protein Unfolding is a Precursor of Protein Aggregation. Issue 5 (3rd February 2020) - Bianco, Valentino; Franzese, Giancarlo; Coluzza, Ivan
Abstract: We present a computational study on the folding and aggregation of proteins in an aqueous environment, as a function of its concentration. We show how the increase of the concentration of individual protein species can induce a partial unfolding of the native conformation without the occurrence of aggregates. A further increment of the protein concentration results in the complete loss of the folded structures and induces the formation of protein aggregates. We discuss the effect of the protein interface on the water fluctuations in the protein hydration shell and their relevance in the protein‐protein interaction. Abstract : A computational study on the folding and aggregation of proteins in an aqueous environment as a function of the concentration is presented.